#TITLE_ALTERNATIVE# - SRI BAWONO AJI ( 15110051 ); Pembimbing : Dr. Ir. Kosasih Prijatna, M.Sc., WISNU
Borobudur Temple is the world's cultural heritage objects that have been recognized by UNSECO. The recognition cause the attention on Borobudur is increasing. Besides being a tourist attraction, Borobudur also become the research object in several disciplines, including archeology and architecture. However, information about Borobudur is still limited and there is no container that stores all of the information. One way to overcome these obstacles is by create a database of Borobudur temple. The database contains a collection of information about the objects making up the Borobudur Temple. Besides storing information in the form of text and numbers, the database also stores information in the form of three-dimensional models.